Pengaruh dark triad personality terhadap perilaku cyberbullying: Empati dan regulasi emosi sebagai mediator: The influence of dark triad personality on cyberbullying behavior: Empathy and emotional regulation as mediators - Safaria, Triantoro; Bashori, Khoiruddin (Persona:Jurnal Psikologi Indonesia, 2023)
Currently, cyberbullying remains a problem globally. This issue is prevalent among teenagers. Several studies have explored this problem, but none have attempted to test the theoretical model of the dark triad personality, empathy, and emotional regulation on cyberbullying. This research aims to test a model involving cyberbullying, dark triad personality, empathy, and emotional regulation as mediators. A total of 309 out of 1205 high school students from two private schools (207 students) and one public school (102 students) in Yogyakarta voluntarily participated in this study. Purposive sampling was used to recruit respondents. The cyberbullying scale (α = .932), dark triad personality scale (α = .752), empathy scale (α = .785), and emotional regulation scale (α = .915) were used to collect data. Content validity and internal consistency reliability were applied. Data analysis was conducted using Structural Equation Modeling (SEM) with Amos 12 software. The results of this study indicate that the model of dark triad personality, empathy, and emotional regulation as mediators of cyberbullying behaviour produces a well-fitting model with its empirical data (CMIN=.747, p=862, RMSEA= .000, GFI= .999). Emotional regulation and empathy partially mediate the influence of psychopathy and narcissism on cyberbullying behaviour. Psychopathy is the only personality trait of the dark triad that directly or indirectly affects cyberbullying. The implications of the research are the need to develop interventions to reduce the dark triad personality traits and enhance empathy and emotional regulation in adolescents, in order to avoid cyberbullying behavior.